Особливості соціалізації дітей у різновікових групах ЗДО - Пащенко, Валентина Григорівна (My University, 2020)
Магістерська робота на тему: «Особливості соціалізації дітей у різновіковій групі закладу дошкільної освіти»досліджувалася на теоретич¬ному та емпіричному рівнях. На теоретичному рівні здійснене теоретичне обґрунтування проблеми соціалізації дітей дошкільного віку у різновіковій групі. На емпіричному рівніпредставлена програма й методика констату-вального, формувального й контрольного етапів педагогічного експерименту. В межах цієї частини роботи, розроблені критерії, показники соціалізації дітей у різновіковій групі ЗДО, окреслені й охарактеризовані рівні її сформованості: низький, середній, високий. Підібрані й розроблені методики для практичного вивчення станусформованості соціалізації дітей різновікової групи у практиці сучасних закладів дошкільної освіти. Розроблені й перевірені педагогічні умови соціалізації дітей у різновікових групах дошкільного закладу
Master’s thesis on the topic: "Peculiarities of children’s socialization in different age groups of preschool education" was studied at the theoretical and empirical levels. At the theoretical level, the theoretical substantiation problem of children’s socialization of preschool in different age groups is carried out. At the empirical level the program and a methodology of a statement, forming and control stages of pedagogical experiment are presented. Within this part of the work, criteria, indicators of children’s socialization in the age group of children are developed, the levels of its formation are outlined and characterized: low, medium and high. Methods for practical study of the state formation children’s socialization of the different ages into practice of modern preschool are selected and developed. The pedagogical conditions of children’s socialization in different age groups of preschool are developed and checked. Keywords: socialization, socialization of children, age group of children, preschool
Keywords: соціалізація дітей; різновікова група дітей